2010
DOI: 10.1111/j.1600-0447.2009.01460.x
|View full text |Cite
|
Sign up to set email alerts
|

Impulsive aggression in adults with attention‐deficit/hyperactivity disorder

Abstract: Dowson JH, Blackwell AD. Impulsive aggression in adults with attention-deficit ⁄ hyperactivity disorder.Objective: DSM-IV criteria for attention-deficit ⁄ hyperactivity disorder (ADHD) include examples of ÔimpulsivityÕ. This term can refer to various dysfunctional behaviours, including some examples of aggressive behaviour. However, impulsive aggression is not included in the DSM-IV criteria for ADHD. The associations of impulsive aggression with ADHD were investigated. Method: Seventy-three male adults with D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 41 publications
3
27
0
2
Order By: Relevance
“…These results resemble findings from studies with ADHD children and adolescents, which have reported a closer relation of ADHD with reactive aggression than with proactive aggression (Bennett et al 2004;Waschbusch and Willoughby 2007). Likewise, Dowson and Blackwell (2010) recently reported findings from a study with adults with ADHD, which indicate that ADHD is a predictor for comorbid impulsive aggression.…”
Section: Modelsupporting
confidence: 86%
“…These results resemble findings from studies with ADHD children and adolescents, which have reported a closer relation of ADHD with reactive aggression than with proactive aggression (Bennett et al 2004;Waschbusch and Willoughby 2007). Likewise, Dowson and Blackwell (2010) recently reported findings from a study with adults with ADHD, which indicate that ADHD is a predictor for comorbid impulsive aggression.…”
Section: Modelsupporting
confidence: 86%
“…In a more recent study by the same research group, Dowson and Blackwell [44] investigated impulsive aggression in 73 adults with DSM-IV ADHD adults (mean age of 29). Using questionnaires, they looked at both externally directed aggression and autoaggression.…”
Section: Resultsmentioning
confidence: 99%
“…Only three studies used a sample of adults (older than 18 years) [43-45], of which two were by the same research group [43,44]. Given what has just been described about the potential effect of age on ADHD symptoms, more studies are required which use samples to include older people in order to elucidate the effect of ADHD over the course of their lifetime.…”
Section: Discussionmentioning
confidence: 99%
“…There is a high prevalence of psychological problems in the parents of children with ADHD, especially adult ADHD itself 15 , but also depression, anxiety 16 and aggression. 17 Maternal depression is associated with parental criticism and hostility 18 and aggression in parents is linked to poor parenting practices. 19 The final question to be addressed relates to the extent to which different aspects of EE show a similar set of shared familial and child specific influences.…”
Section: Introductionmentioning
confidence: 99%